Status gizi, aktivitas fisik, dan prestasi akademik siswa SMA gakin dan non-gakin di Kota Bitung - Daniel Robert; Abidillah Mursyid; Emy Huriyati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2007)
Background: A good nutritional status of students will greatly support their physical activities. Social economic status of a family may affect intake of nutrient, energy, and protein which can bring impact on nutritional status. Good nutritional status is necessary for teenagers to maintain health and support physical activities. Senior high school students from poor and non poor families may have different nutritional status, physical activities, and academic achievement.Objectives: The objectives of the study were to identify differences in nutritional status, physical activities, and academic achievement of students from poor and non poor families at Bitung Municipality and relationship between intake of energy and protein and nutritional status, physical activities, and academic achievement of students from poor and non poor families.Methods: The study was observational with cross sectional design. Population and samples were senior high school students of 16–18 years old (from database) from poor and non poor families. Total samples were 314 students taken using stratified random sampling technique. The study was conducted in September–December 2005. Data were analyzed using chi-square, t-test, and linear regression with significance level 95% and processed using computer software.Results: There was a significant difference in nutritional status, light physical activity, academic achievement in poor and non poor highschool students (p<0,05), but there was no significant difference in the medium and heavy physical activity (p>0,05). There was also a relationship between confounding variable of energy intake with nutritional status, father’s job with light activity, father’s education and job with medium activity, father and mother’s education, father’s job, and energy intake with academic achievement. There was no relationship between confounding variable with heavy physical activity (p>0,05).Conclusion: There was differences in nutritional status in light physical activity and academic achievement between students from poor and those from non poor families.